Titanium-protein nanocomposites as new biomaterials produced by high-pressure torsion - Floriano, Ricardo; Edalati, Kaveh; Pereira, Karina Danielle; Luchessi, Augusto Ducati [UNESP] (Springer Nature, 2023)
The development of new biomaterials with outstanding mechanical properties and high biocompatibility has been a significant challenge in the last decades. Nanocrystalline metals have provided new opportunities in producing high-strength biomaterials, but the biocompatibility of these nanometals needs to be improved. In this study, we introduce metal-protein nanocomposites as high-strength biomaterials with superior biocompatibility. Small proportions of bovine serum albumin (2 and 5 vol%), an abundant protein in the mammalian body, are added to titanium, and two nanocomposites are synthesized using a severe plastic deformation process of high-pressure torsion. These new biomaterials show not only a high hardness similar to nanocrystalline pure titanium but also exhibit better biocompatibility (including cellular metabolic activity, cell cycle parameters and DNA fragmentation profile) compared to nano-titanium. These results introduce a pathway to design new biocompatible composites by employing compounds from the human body.